Lessons learned from screening potential other effective area‐based conservation measures - Carly N. Cook; Madhu Rao; Peter J. Clyne; Vanessa Rathbone; Christian Barrientos; Antonio Boveda; Alex Diment; Jorge Parra; Valeria Falabella; Matthew Linke; Deo Kujirakwinja; Stephane Ostrowski; et al. (Conservation Biology, 2026)
Other effective area‐based conservation measures (OECMs) are sites that deliver effective biodiversity outcomes irrespective of their management objectives. These areas are widely expected to play an important role in efforts to protect 30% of Earth by 2030. Despite general guidance to support screening sites against the formal criteria to be OECMs, progress recognizing sites has been limited. To advance the ability to identify OECMs, we developed a questionnaire that translates the components of the broad formal guidance into statements that experts can use to screen potential OECMs. Twenty‐eight local experts used the questionnaire to evaluate a large global sample of 81 sites. Most sites evaluated were largely in good condition and had the potential to achieve conservation outcomes, but none met the criteria to be considered OECMs. The most common challenges are related to threat management, adequate resourcing, and the ability to demonstrate that governance and management are achieving effective and sustained conservation outcomes. Based on the formal International Union for Conservation of Nature guidance, sites that only partially meet the relevant criteria remain candidate OECMs. Our questionnaire provides a nuanced way to assess OECMs that can help identify what support sites need to meet the necessary criteria. With effective long‐term conservation outcomes unable to be demonstrated for so many important conservation areas, our findings raise important questions about how to ensure area‐based conservation promotes positive and sustained outcomes for biodiversity.